Evidence for the recognition of two species of Anolis formerly referred to as A. tropidogaster (Squamata: Dactyloidae) - Köhler, Gunther; Batista, Abel; Vesely, Milan; Ponce, Marcos; Carrizo, Arcadio; Lotzkat, Sebastian (Zootaxa, 2012)
Based on differences in hemipenial morphology, male dewlap coloration, pholidosis, and 16S mtDNA, we recognize twospecies of anoles related to what was formerly referred to as Anolis tropidogaster: Anolis tropidogaster Hallowell 1856and A. gaigei Ruthven 1916. The hemipenis in A. tropidogaster is large, bulbous, and bilobed whereas it is small, thin,and unilobed in A. gaigei; the male dewlap is almost uniform purplish red, sometimes with a paler orange central area inA. tropidogaster versus orange yellow with a darker orange central area in A. gaigei; and—aside from more subtle differ-ences in several pholidotic characteristics—in male A. gaigei there is a pair of greatly enlarged postcloacal scales whichis absent in A. tropidogaster. In the western part of its geographic range, A. gaigei has been confused with another anolespecies, A. polylepis Peters 1873, from which it can be readily distinguished by its strongly keeled ventral scales (smooth in A. polylepis).